On the high‐gasification rate of Brazilian manganese ore in chemical‐looping combustion (CLC) for solid fuels. Issue 11 (28th June 2013) - Frohn, Peter; Arjmand, Mehdi; Azimi, Golnar; Leion, Henrik; Mattisson, Tobias; Lyngfelt, Anders
<x xml:space="preserve">Abstract</x> The high rate of char gasification observed when using a Brazilian manganese ore as compared to ilmenite is investigated in a batch fluidized‐bed reactor. Experiments were carried out at 970°C using petroleum coke, coal and wood char as fuel with a 50% H2O in N2 as fluidizing gas. A manufactured manganese oxygen carrier was also used, however, which presented a slower char conversion rate than the manganese ore. It is concluded that decrease in H2 inhibition and oxygen release are unlikely to be the main responsible mechanisms for the ore's unexpected gasification rate. The ore was also mixed in different ratios with ilmenite and it was observed that the presence of even small amounts of ore in the bed resulted in increased gasification rate. Thus, the high‐gasification rate for the manganese ore could be due to a contribution from the impurities in the ore by catalyzing the gasification reaction. © 2013 American Institute of Chemical Engineers AIChE J, 59: 4346–4354, 2013